Project Work to Promote Language Learning - Meganathan, R. (JOURNAL OF INDIAN EDUCATION, 2011)
Language learning is aimed at making learners use the language for real life purposes. This is not limited to using of language(s) for communicative purpose only; learners need to use language to function in professional, academic and social settings. This demands higher order language and thinking skills. Nature and characteristics of the classroom has to change to meet this demand and teachers have to explore ways and means of enabling learners ‘engage’ with language(s) in and out of the classroom. Tasks, activities and assignments are to be conceived of not in the conventional teacher dominated sense; they need to help learners in noticing the form and meaning of language(s) by using it in real life activities/task. Project work of this nature would help in promoting language learning. This paper attempts to make a case for projects for language learning and discusses the possible ways and means of designing and carrying out projects as language learning tasks where learners work with language for a period of time. At the end, it also provides a list of projects which could be carried out at different stage of schooling.